FUNCTION AND ITS PROPERTIES (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2026)
This article discusses the concept of a function, its basic properties, graphs, types, and applications in mathematical and practical problems.